The Effect of Brisk Walking Exercise on Blood Pressure in Hypertension Patients at Muhammadiyah Gresik Hospital - Islami, Mufatachul; Sari, Diah Jerita Eka; Widiharti, Widiharti; Fitrianur, Widya Lita (OJS Universitas Muhammadiyah Gresik, 2024)
One of the non-communicable diseases that is very serious and experienced by many people is hypertension, pharmacological therapy often fails in practice because hypertensive patients are lazy to take medication, forget to take medication/difficulty accessing medication. One type of non-pharmacological therapy to assist in controlling blood pressure is to carry out brisk walking exercise routinely. Objective: To analyze the effect of brisk walking exercise on changes in blood pressure in hypertensive patients at Muhammidyah Gresik Hospital. The design of this study used a quasy experiment with a one-group pre-posttest design approach. The population was all high blood pressure sufferers at Muhammadiyah Gresik Hospital, a sample of 36 patients with a sampling technique using simple random sampling. Data collection using questionnaires and SOP and data analysis using paired t test From the results of the study, the average blood pressure measurement results for the majority of patients who did the brisk walking exercise at the Muhammadiyah Gresik MAP Hospital (pretest) in the study patients was 124.7mmHg. From these results it was found that there was an average decrease in MAP (posttest) blood pressure in patients by 120mmHg. From the results of the paired t test, the PValue was 0.001 <α (0.05). There is an effect of the brisk walking exercise on changes in blood pressure in hypertensive patients at the Muhammadiyah Gresik Hospital.